2016
DOI: 10.7205/milmed-d-15-00028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Uniform Design on the Speed of Combat Tourniquet Application: A Simulation Study

Abstract: The closure system of pockets on the combat uniform might influence the time taken to apply a tourniquet. Regular training might also reduce the time taken to apply a tourniquet effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Uniforms equipped with special pockets for quick and uncomplicated access to the stasis significantly reduces the time required for self-use. [16,17] The tourniquet was used only after other methods of bleeding control failed. It presented tourniquet application when providing assistance to a soldier in the danger zone even when under fire.…”
Section: Discussionmentioning
confidence: 99%
“…Uniforms equipped with special pockets for quick and uncomplicated access to the stasis significantly reduces the time required for self-use. [16,17] The tourniquet was used only after other methods of bleeding control failed. It presented tourniquet application when providing assistance to a soldier in the danger zone even when under fire.…”
Section: Discussionmentioning
confidence: 99%
“…In the tactical tourniquet training programs, soldiers are trained to both pre-position and prepare. Higgs, et al have demonstrated that access modalities of the tourniquet might influence the time taken to apply it 14 . This study compared the differences in CAT placement time between American and Australian soldiers.…”
Section: Discussionmentioning
confidence: 93%
“…, 11 , 19 , 24 , 25 To the best of the authors’ knowledge, this study is the first to precisely highlight the influence of such a long delay on the learning of the tourniquet’s use. This notion has been suggested by the work of Higgs, et al 14 In addition to measuring the tourniquet “hands-on” time of the American and Australian soldiers, the authors also measured the time of tourniquet application. This study was carried out in simulation, in the theater of military operations.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations